Post operative wound gape in obstetric and gynaecological surgeries - Vijay, Aswathi; Chilkund, Jayanth; Siddhi Kore; Saroj Kumari (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: Despite advances made in asepsis, post operative wound infection is one of the major causes for increased postoperative morbidity and huge economic burden for patient and healthcare. This study was undertaken to identify risk factors for the post operative wound gaping in obstetrical and gynaecological surgeries. Methods: Retrospective observational study was conducted in the department of obstetrics and gynaecology of Pt. Madan Mohan Malviya Shatabdi hospital, Govandi, Mumbai for the year 2022. Results: 1611 cases were analysed that underwent various obstetrical and gynaecological surgeries. Post operative wound gaping incidence was 1.5 %. Most of the cases were seen in less than 34 years of age. 21% of cases reported with wound gaping and discharge within 5-7 days of surgery while 79% of cases reported gape after 7 days of surgery. 54% cases with wound gape were obstetric. The most commonly known associated risk factor was found to be diabetes mellitus (12.5%) followed by anaemia (8.3%), obesity (4.2%) and hypertension (4.2%). 62.49% of post operative surgical wound gape were multiparous. It is seen that in all these cases of wound gape the subcutaneous tissue was sutured separately as a layer with absorbable suture material- Vicryl no 1-0 or Vicryl no 2-0. Conclusions: Factors affecting post operative wound gaping are diabetes mellitus, anaemia, hypertension, obesity, chemoprophylaxis given prior to surgery, surgical method of wound closure and type of surgery. Standard wound closure techniques, correction of the avoidable known risk factors would provide a better outcome.